2021
DOI: 10.3389/fphys.2021.744272
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid, a Plant Hormone, Suppresses Phytophagous Insect Immune Response by Interrupting HMG-Like DSP1

Abstract: Salicylic acid is a plant hormone that can mediate various plant physiological processes. Salicylic acid can bind to human high mobility group box 1 (HMGB1) and interrupt its role in mediating immune responses. Dorsal switch protein 1 (DSP1) is an insect homolog of HMGB1. In this study, a DSP1 (Se-DSP1) encoded in Spodoptera exigua, a phytophagous insect, was characterized, and its potential role in immune response was explored. Upon bacterial challenge, Se-DSP1 was localized in the nucleus and released into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…Upon the fungal infection, F. occidentalis expressed immune responses by activating DSP1, an ortholog of vertebrate HMGB1 known to act as a damage signal in response to pathogen infection in insects ( 31 ). HMGB1 is ubiquitously expressed and localized in the nucleus to bind to DNA for regulating gene expression through chromatin remodeling ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon the fungal infection, F. occidentalis expressed immune responses by activating DSP1, an ortholog of vertebrate HMGB1 known to act as a damage signal in response to pathogen infection in insects ( 31 ). HMGB1 is ubiquitously expressed and localized in the nucleus to bind to DNA for regulating gene expression through chromatin remodeling ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can activate PLA 2 to mediate various immune responses ( 16 ). Later, Mollah et al ( 31 ) showed that DSP1 activates Toll immune signalling to PLA 2 activation via Pelle kinase in S. exigua . In F. occidentalis in our current study, DSP1 was obtained from its genome and its expression was confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, S. frugiperda invasions were reported in western Korea, intimidating the crop yields of rice and corn [ 29 ]. A highly virulent strain of X. hominickii was found from a comparative toxicological analysis and used to replace a previous IBC agent to control S. exigua [ 30 ]. Thus, this study was devised to develop a highly efficient IBC agent against spodopteran insect pests without hazards to humans or the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Gibberellin (GA) controls seed germination and plays an important role in the 'green revolution' [8]. Salicylic acid (SA) and jasmonic acid (JA) act as the important signal molecules during the immune and defense responses of plants [9,10].…”
Section: Introductionmentioning
confidence: 99%